QUR’ANIC ECONOMIC INTERPRETATION USING A THEMATIC EXEGESIS APPROACH TO ADDRESS THE RISE OF DIGITAL FRAUD AND CYBERCRIME ON SOCIAL MEDIA - Mukhtar Yunus (Journal Analytica Islamica, 2024)
The rise of digital fraud and cybercrime on social media in 2024 has become a serious threat to the economic stability and social security of Indonesian society. Phishing, fraudulent investment schemes, illegal trade, and the exploitation of personal data through digital platforms have become increasingly widespread, with more sophisticated and systematic modes of operation. This study aims to interpret Qur’anic economic verses through a thematic exegesis approach in order to identify theological and ethical foundations for addressing these problems. The method used is library research with a thematic exegesis approach (al-tafsīr al-mawḍū‘ī), which collects and analyzes Qur’anic verses related to economics, transactions, and business ethics. The findings show that the Qur’an provides a comprehensive conceptual framework through the principles of honesty (al-ṣidq), justice (al-‘adl), transparency (al-waḍāḥah), and the prohibition of fraud (al-ghish). Verses such as QS. al-Baqarah [2]: 188, QS. an-Nisā’ [4]: 29, QS. al-Muṭaffifīn [83]: 1–6, and QS. al-Anfāl [8]: 27 provide a strong moral foundation for developing spiritually based digital literacy. This study concludes that Qur’anic economic interpretation using a thematic exegesis approach offers a holistic solution by integrating the sacred dimension of religious texts with the profane dimension of contemporary digital realities, thereby fostering collective public awareness in combating digital crime through the strengthening of Islamic economic character.